New paradigms and recurring paradoxes in education for citizenship an international comparison - Steiner-Khamsi, Gita; Torney-Purta, Judith, 1937-; Schwille, John (International perspectives on education and society ;, 2002)
Scholars in international comparative education are calling for a new paradigm - a multi-level qualitative analysis of cross-national data. In response, this volume demonstrates the application of a multi-level analysis to qualitative data. Based on an international data base and case studies on civic education in 24 countries that were gathered in the IEA Civic Education Study, scholars in civic education and international comparative education identify, analyze, and discuss three areas: first, the nature and status of civic education within countries, as well as common themes across countries; second, the paradoxes, puzzles, and complexities presented within countries; and third, new paradigms and methodologies for qualitative cross-national analyses. This work contributes to both the content of research in civic education and the methodology of research in international comparative education. Political systems of participating countries include those that are historically of a free-market orientation, as well as those of formerly socialist countries that have, in the 1990s, undergone massive political and economic change.